2004
DOI: 10.1007/s00467-004-1538-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentoxifylline in Adriamycin-induced renal disease in rats

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a mediator of inflammation in human and animal renal disease. Pentoxiphylline (PTX) is an inhibitor of TNF-alpha. In this study we examined the effects of PTX on TNF-alpha, proteinuria, nitrite production, and apoptosis in an experimental model of Adriamycin (ADR) nephropathy in rats. Rats were divided into four groups: untreated Wistar rats (controls), PTX treatment alone, ADR treatment alone to induce nephropathy, and ADR treatment followed by PTX. ADR treatment fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…DOX‐treatment significantly increased serum creatinine, BUN, NO, urinary albumin, and NAG. Our results are in good agreement with those previously reported 36–38. However, treatment with AG (200 or 400 mg/kg) resulted in a significant decrease of these parameters in DOX‐treated animals, thus offering considerable protection against nephrotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…DOX‐treatment significantly increased serum creatinine, BUN, NO, urinary albumin, and NAG. Our results are in good agreement with those previously reported 36–38. However, treatment with AG (200 or 400 mg/kg) resulted in a significant decrease of these parameters in DOX‐treated animals, thus offering considerable protection against nephrotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, DOX treatment caused a significant increase in TBARS levels and a significant decrease in GSH and CAT levels, when compared with the control group. These findings are in agreement with previous reports [25,29]. TBARS, a stable metabolite of the free radical mediated lipid peroxidation cascade, is widely used as a marker of oxidative stress and lipid layer destruction [30].…”
Section: Discussionsupporting
confidence: 93%
“…22 PTX was shown to prevent apoptosis in methotrexate, Adriamycin and cisplatin-induced nephropathies in various experimental studies. 13,22,23 In our study, we showed that PTX significantly ameliorates GEN-induced apoptosis. These data support the hypothesis that PTX protects kidney tissue against apoptosis caused by GEN treatment.…”
Section: Discussionmentioning
confidence: 76%
“…11 Pentoxifylline (PTX) is a methylxanthine derivative, which has well-known renoprotective effects through the prevention of free radical formation and inhibition of programmed cell death. [12][13][14] Recently, PTX has been shown to be protective in amikacin and GEN-induced nephrotoxicity. 15,16 In amikacin-induced nephrotoxicity, it has been shown that PTX has renoprotective effects through antioxidative mechanisms and that was not studied in GEN-induced nephrotoxicity model.…”
Section: Introductionmentioning
confidence: 99%